2010
DOI: 10.1111/j.1095-8339.2010.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Atlantic Forest trees: fragmentation effects on Astronium graveolens (Anacardiaceae) and Metrodorea nigra (Rutaceae), species with distinct seed dispersal strategies

Abstract: We explore the genetic structure and variability in autochorous Metrodorea nigra (Rutaceae) and anemochorous Astronium graveolens (Anacardiaceae), two species affected by deforestation in the Atlantic Forest of Brazil. The effects of deforestation and the depletion of the habitat within the remaining patches of forest are evaluated by comparing the variability between saplings and adults of each of these two species. The results indicate that the depletion of forest land and the deteriorating condition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
(43 reference statements)
0
13
0
2
Order By: Relevance
“…Schwarcz et al (2010) found values of H O and H E of 0.633 and 0.224, respectively, in natural populations of M. nigra in the São Paulo State using allozyme markers. These values were much lower than those found in the present study.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Schwarcz et al (2010) found values of H O and H E of 0.633 and 0.224, respectively, in natural populations of M. nigra in the São Paulo State using allozyme markers. These values were much lower than those found in the present study.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Metrodorea nigra is often present in high population density; several authors have described its ecological importance and ability to adapt to conditions of the understory of the semideciduous seasonal forest (Durigan et al, 2000;Villela et al, 2006;Cassola, 2008). It is considered to be a key species in the nutrients dynamics of this type of forest (Villela et al, 2006) and its presence is associated with the occurrence of large late-successional trees (Durigan et al, 2000;Bertoncini, 2003;Kotchetkoff-Henriques, 2003, Cassola, 2008Schwarcz et al, 2010). However, under conditions of fragmentation, open glades, and selective logging, the population is reduced (Bertoncini, 2003;Villela et al, 2006) or completely disappears (Cassola, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such a pattern has also been recorded for other tree species (FARWIG, 2008;ORTEGO et al, 2010), as well as a cycad (OCTAVIO-AGUILAR, 2009). Yet post-fragmentation cohorts do not always display higher levels of differentiation than their pre-fragmentation counterparts: a number of studies have found low levels of differentiation for both cohorts (LATOUCHE-HALLÉ, 2003;SCHWARCZ et al, 2010), sometimes still with significantly higher values for juveniles than adults (RIBEIRO et al, 2005;FIGUEROA-ESQUIVEL, 2010). Alternatively, both may display high differentiation, for example where populations are naturally fragmented (KETTLE et al, 2008).…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 99%
“…It is recommended for forest densification in landscaping and restoration of degraded areas and legal reserve (Lorenzi, 2008). Only one study of genetic diversity using isoenzymes has been carried out with populations of this species (Schwarcz et al, 2010); therefore, very little is known about the population genetic structure and gene flow of the M. nigra species. This species is commonly found in the most conserved and shaded parts of semideciduous forests and their small size facilitates access to flowers, which raises the possibility of being used as a model species for fine-scale genetic studies, to quantify the effects of habitat fragmentation and to guide conservation strategies.…”
Section: Introductionmentioning
confidence: 99%